1999
DOI: 10.1046/j.1365-263x.1999.00130.x
|View full text |Cite
|
Sign up to set email alerts
|

Child protection: a survey of experience and knowledge within the dental profession of New South Wales, Australia

Abstract: Further education and training is required for both the dental profession and the child protection agencies to improve the inter-agency working relationship and thus provide better protection for children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
35
1
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 7 publications
13
35
1
1
Order By: Relevance
“…Just over one third (34%) of respondents had suspected child abuse in one or more patients during their careers. This is comparable to the Scottish survey 12 and other international studies 17,18 but lower than reported levels in USA dentists. 19 The majority of DTs (83%) had recorded their fi ndings in the dental notes and again this is higher than the corresponding 56% in the Scottish survey.…”
Section: Practicesupporting
confidence: 80%
See 4 more Smart Citations
“…Just over one third (34%) of respondents had suspected child abuse in one or more patients during their careers. This is comparable to the Scottish survey 12 and other international studies 17,18 but lower than reported levels in USA dentists. 19 The majority of DTs (83%) had recorded their fi ndings in the dental notes and again this is higher than the corresponding 56% in the Scottish survey.…”
Section: Practicesupporting
confidence: 80%
“…This may refl ect the fact that the majority of DTs are still likely to be employees in the GDS or salaried practitioners. 15 A recurring theme in this study and in previous work 12,14,[17][18][19] is the role of uncertainty in preventing referral. As demonstrated here, the uncertainty can be related to knowledge of the condition, the processes for referral and the consequences of referral in the broadest sense.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations